Yếu tố tác động đến chất lượng đào tạo tại khoa Anh-Pháp-Đức: góc nhìn từ phía người học = Factors affecting training quality in the Department of English studies, Department of French studies, and Department of German studies: perspectives from students /Phạm Ngọc Thạch. - Phạm Ngọc Thạch.
It is important that leaders, administrators, teachers and students of educational institutions be involved in training quality improvement. This paper analyzes the results gained from a survey on teaching quality of some subjects offered for over 1,200 second-year and third-year students from English Department, France Department and German Department at Hanoi University within 2016-2017. By applying frequency analysis method, T-test and logistic regression model as well as the perspective of ASEAN University Network – Quality Assurance (AUN-QA) on training quality at institutional level, the author compares the teaching quality of some subjects at the three departments, then proposes recommendations for teaching from three aspects: course organization, lecturers and exams, testing and assessment.